Opting-in to Prosocial Incentives - Daniel Schwartz; Elizabeth A. Keenan; Alex Imas; Ayelet Gneezy (Center for Economic Studies and ifo Institute (CESifo), 2017)
Prior work has demonstrated that prosocial incentives – where individuals' effort benefits a charitable organization – can be more effective than standard incentives, particularly when the stakes are low. Yet, little is known about the effectiveness of prosocial incentives on people's decisions to participate or opt-in to the incentivized activity in the first place. We examined the effectiveness of prosocial incentives on people's participation decisions using two distinct field experiments, one that sought to encourage recycling and the other that incentivized completion of effortful tasks. Across both studies, we found that individuals were more likely to avoid activities that involved prosocial incentives, compared to standard incentives, regardless of incentive size, and even when the donation was optional. Our results identify a significant limit for the scope of prosocial incentives as effective motivation tools.
Keywords: 330; decision making; incentives; prosocial behavior; field experiments